Size‐Dependent Piezoelectric Properties of Electrospun BaTiO3 for Enhanced Energy Harvesting. (27th October 2017) - Shirazi, Paymon; Ico, Gerardo; Anderson, Christopher S.; Ma, Meghann C.; Kim, Bum Sung; Nam, Jin; Myung, Nosang V.
Abstract: In this study, electrospinning is used to fabricate a nanofibrous structured mixture of barium and titanium precursors dissolved in poly(vinylpyrrolidone). Two separate experimental designs are conducted to optimize the reduction of fiber diameter with minimum defects. The first focuses on the optimization of the solution properties and electrospinning parameters. The second is employed to optimize environmental conditions to further reduce the fiber diameter. Morphological analysis shows a minimum average fiber diameter of 77 ± 15 nm with minimal beading. The as‐spun nanofibers are subsequently calcinated to produce barium titanate nanofibers with an average diameter of 45 ± 9 nm. As expected, the average grain size increases as the heat treatment duration increases. Piezoresponse force microscopy reveals that the fiber diameter is inversely related to the d 33 piezoelectric coefficient. Individual crystallites of 25 nm in size along the axis of the 48 nm fiber exhibit d 33 coefficients as high as 76 pm V −1 . A flexible piezoelectric device composed of nanofibers with an average diameter of 45 nm embedded within polydimethylsiloxane produces a maximum voltage and power output of 7.94 Vp–p and 1.95 µW cm −2, respectively, at a load resistance of 3.33 MΩ and a strain of 0.16%. Abstract : The piezoelectric properties of electrospun barium titanate depend on the dimensions of the nanofibers. Here, they are controlled by using an optimized process, presenting a step towards the development of high‐performance 1D materials. At a fiber diameter of 45 nm, approaching the size of a single grain, the directional uniformity of piezoelectric domains along the fiber axis enhances the piezoelectric constant of barium titanate.